Role of Fission Yeast Tup1-like Repressors and Prr1 Transcription Factor in Response to Salt Stress - Greenall, Amanda (The American Society for Cell Biology, 2002)
In Schizosaccharomyces pombe, the Sty1 mitogen-activated protein kinase and the Atf1 transcription factor control transcriptional induction in response to elevated salt concentrations. Herein, we demonstrate that two repressors, Tup11 and Tup12, and the Prr1 transcription factor also function in the response to salt shock. We find that deletion of both tup genes together results in hypersensitivity to elevated cation concentrations (K(+) and Ca(2+)) and we identify cta3(+), which encodes an intracellular cation transporter, as a novel stress gene whose expression is positively controlled by the Sty1 pathway and negatively regulated by Tup repressors. The expression of cta3(+) is maintained at low levels by the Tup repressors, and relief from repression requires the Sty1, Atf1, and Prr1. Prr1 is also required for KCl-mediated induction of several other Sty1-dependent genes such as gpx1(+) and ctt1(+). Surprisingly, the KCl-mediated induction of cta3(+) expression occurs independently of Sty1 in a tup11Δ tup12Δ mutant and so the Tup repressors link induction to the Sty1 pathway. We also report that in contrast to a number of other Sty1- and Atf1-dependent genes, the expression of cta3(+) is induced only by high salt concentrations. However, in the absence of the Tup repressors this specificity is lost and a range of stresses induces cta3(+) expression.